Intradural Extramedullary Spinal Cord Tumors and Outcome with Surgical Approach: A Single Centre Retrospective Study - Dea Alberta Setiawati; Hanis Setyono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Intradural extramedullary spinal tumor (IDEM) is rare compared to all neoplasms of the central nervous system; however, it is the most common type of primary intraspinal neoplasms. Most tumors are meningioma, schwannoma, and neurofibroma. IDEM tumor has a predilection in women with ages ranging from 40-60 years. This study was conducted to describe the outcome of patients with IDEM tumors after surgery in Dr. Moewardi General Hospital from 2019-2022. Methods: This retrospective descriptive study was conducted in 2019-2022. Forty-four patients diagnosed with IDEM tumors and who underwent surgical approach were included. The studied variables include age, pathological diagnosis, intervention, and postoperative follow-up. Results: Most subjects were within the age range of 40-60 years old (52.3%), women (63.6%), and had schwannoma (45.5%), followed by meningioma (25%). Based on gender, both men and women mostly had schwannoma (56.25% and 39.3%, respectively). All subjects underwent tumor excision laminectomy. In the follow-up, most subjects (86.4%) had improved clinical symptoms after surgery. Conclusion: Intradural extramedullary spinal tumors mostly occur in women 40-60 years old, and schwannoma and meningioma are the most frequent types. Laminectomy intervention can provide clinical symptom improvement in most patients.